Online political parody in Thailand: Political communication under the computer crime act (No.2) 2017 - Pimonpan Chainan (2020)
© The Author(s) 2020. Since the military coup in 2014, Thailand has entered a tense political atmosphere, and the population has been under control of the junta. Consequently, political communication on the Internet has been in steep decline, resulting from the implementation of the Computer Crime Act (No.2) 2017. This implies that people have been practising self-censorship as they have witnessed cases which scholars, politicians, and activists who strongly criticised the authorities were prosecuted, and they were filled with fear that they will be imposed the same penalty if they violate the act. Given these points, this study examines political communication in the form of political parody and satirical comic strips in social media. Data was collected from the Facebook page “Emphasis Type=“Italic”Khai Maew X Emphasis” and then processed using content analysis to show patterns, points, and the significance of political communication. Additionally, an in-depth interview with relevant individuals was conducted to gather primary data to incorporate into the analysis. Political satire generally surfaces at times when people’s freedom is restricted since they cannot directly express their thoughts against injustice, hegemonic politicians, and government. In other words, indirect political communication is established in the form of satire and parody, allowing media users to relate the presented issues to current political affairs. Although political satire and parody may not lead to actual social change, it is the initial phase of exposing and questioning the existing social problems and can be considered a struggle against the state government. Through the nature of social media allowing anonymous authors, the authors’ and users’ interactions can be taken as an accurate reflection of the country’s current state of freedom during its political transformation.